PARENTING STYLE BERBASIS REGULASI EMOSI DALAM PRAKTIK KONSELING TERAPAN: STUDI LITERATUR INTEGRATIF TAHUN 2020-2025 - Lisa Lisa; Theresia Mustika Wahyu Hendrati (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Social changes and the increasing complexity of parenting in modern families have made parenting style and emotion regulation important factors in children’s emotional development. This study aims to examine the relationship between parenting style and emotion regulation, as well as its implications for applied counseling practices. The research employed an integrative literature review method by synthesizing various empirical research findings published between 2020 and 2025 from the Google Scholar, Springer, Frontiers, and PLOS databases. The findings indicate that parents’ emotion regulation abilities play an important role in shaping the parenting style they adopt, and that parenting style also contributes to the development of children’s emotion regulation. The authoritative parenting style was identified as the most adaptive approach because it combines appropriate control, warmth, and responsiveness, thereby optimally supporting children’s social-emotional development. A synthesis of findings from Duncan et al. (2010), Jeong et al. (2021), Coyne et al. (2023), and Zitzmann et al. (2024) shows that effective emotion regulation is associated with more supportive parenting, healthier parent-child relationships, and better family psychological well-being. In the Indonesian context, studies by Kumalasari (2021), Alfaeni and Rachmawati (2020), and HJK (2023) indicate that social support, cultural values, and ethnoparenting also influence parenting practices and children’s emotional development. This study concludes that emotion regulation is a fundamental foundation in shaping adaptive parenting styles and is therefore highly relevant to be developed within applied counseling practices to support the quality of family relationships and children’s emotional development. Keywords: parenting style, emotion regulation, mindful parenting, applied counseling, children’s emotional development.   Abstrak: Perubahan sosial dan meningkatnya kompleksitas pengasuhan pada keluarga modern menjadikan parenting style dan regulasi emosi sebagai faktor penting dalam perkembangan emosional anak. Studi ini bertujuan untuk mengkaji hubungan antara parenting style dan regulasi emosi serta implikasinya dalam praktik konseling terapan. Penelitian menggunakan metode studi literatur integratif dengan mensintesis berbagai temuan penelitian empiris yang dipublikasikan pada rentang tahun 2020–2025 melalui database Google Scholar, Springer, Frontiers, dan PLOS. Hasil kajian menunjukkan bahwa kemampuan regulasi emosi orang tua berperan penting dalam membentuk parenting style yang diterapkan, dan parenting style juga berkontribusi terhadap perkembangan regulasi emosi anak. Pola asuh authoritative ditemukan sebagai parenting style yang paling adaptif karena mengombinasikan kontrol yang tepat, kehangatan, dan responsivitas sehingga mendukung perkembangan sosial emosional anak secara optimal. Sintesis temuan Duncan et al. (2010), Jeong et al. (2021), Coyne et al. (2023), dan Zitzmann et al. (2024) menunjukkan bahwa regulasi emosi yang baik berkaitan dengan pengasuhan yang lebih suportif, hubungan orang tua dan anak yang lebih sehat, serta kesejahteraan psikologis keluarga yang lebih baik. Dalam konteks Indonesia, penelitian Kumalasari (2021), Alfaeni dan Rachmawati (2020), serta HJK (2023) menunjukkan bahwa dukungan sosial, nilai budaya, dan etno parenting turut memengaruhi praktik pengasuhan dan perkembangan emosional anak. Studi ini menyimpulkan bahwa regulasi emosi merupakan fondasi penting dalam membentuk parenting style yang adaptif sehingga relevan untuk dikembangkan dalam praktik konseling terapan guna mendukung kualitas hubungan keluarga dan perkembangan emosional anak. Kata kunci: parenting style, regulasi emosi, mindful parenting, konseling terapan, perkembangan emosional anak.